Advanced carbon/flax/epoxy composite material for vehicle applications: vibration testing, finite elements modelling, mechanical and damping characterization. - Ampatzidis, Theofanis (Cranfield University, 2015)
Nowadays, research in automotive and construction industries focuses on materials that offer low density along with superior dynamic and static performance. This goal has led to increasing use of composites in general, and carbon fibre (CF) composites in particular. CF composites have been adopted widely in the space industry and motorsports. However, their high stiffness and low density leads to low damping performance, which is responsible for increased levels of noise and reduction in service life. On the other hand, natural fibres (NF) like flax fibres (FF) are capable of delivering a much better damping performance. A hybrid composite comprising of FF and CF can potentially deliver both on strength and higher damping performance. In this study the mechanical and damping properties of CF, FF and their hybrid composites were examined. Composites' anisotropic nature affects their response to vibrations and so traditional damping experimental setups used for metals had to be ruled out. A damping set up based on Centre Impedance Method (CIM) was adopted for the purpose of this study which was based on an ISO standard originally developed for glass laminates. Standard tensile and flexural tests were conducted in order to characterise the performance of the hybrid composite. The experimental work was accompanied by finite elements analysis (FEA). The experimental data and FEA were used to optimize the hybrid structure layup with respect to damping and structural response.
Keywords: Centre impedance method (CIM); hybrid composites; natural fibre; loss factor; half-bandwidth method; resonant frequency; ISO 16940